WEB-BASED FURNITURE PRODUCT SALES INFORMATION SYSTEM WITH AGILE METHOD (CASE STUDY OF TALENTA UMKM IN TANGGULANGIN SIDOARJO) - Ardi Setiawan; Suhendro Busono (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to design and implement a web-based sales report information system to improve the operational efficiency of Talenta MSMEs, a furniture producer located in Sidoarjo. Background: Currently, Talenta MSMEs rely on manual recording methods for sales and inventory management, which often result in inefficiencies, data inaccuracies, and delays in decision-making. Method: The system is developed using web technologies to enable real-time data processing and accessibility. Key features include daily and monthly sales reports, real-time inventory monitoring, and sales data analysis to support better business insights. Results: The implementation of this information system significantly enhances the accuracy of sales records, streamlines reporting processes, and facilitates timely decision-making. Conclusion: The developed system contributes to improving operational performance and competitiveness, demonstrating how digital transformation can strengthen MSMEs’ business management in the modern era.